Empirical Analysis of Money Demand in Ghana: Implications for Inflation Targeting - Asiam, R.K. (University of Ghana, 2015)
Getting monetary policy right is crucial to the health of any economy (Mishkin, 2004). While the current policy regime is expected to have better control at inflation, certain issues have cast doubt on the effectiveness of the policy regime. As a result, monetary aggregate targeting has surfaced and a commitment has been made to incorporating this in the current policy framework. This has raised the importance of the demand for money function for Ghana again. The study estimates a long run demand for money function, determines the stability of the long run demand for money function and determines the causal links between demand for broad money and the inflation-targeting regime for Ghana. The study uses time series data over the period 1979 to 2014. The cointegration approach by Pesaran et al. (2001) and the causality approach by Toda and Yamamoto (1995) were employed in estimating the models. The Bounds test to cointegration revealed that all the variables in the money demand function – inflation, dollar exchange rates, GDP growth, money supply growth and the inflation-targeting regime converged to long run equilibrium once there were deviations in the short run. Both CUSUM and CUSUMSQ tests showed that this long-run relationship was stable and converged to equilibrium. In the long run, while inflation and money supply were found to negatively impact demand for broad money, the dollar exchange rates and inflation were found to positively impact demand for broad money in the short run. These relationships were statistically significant at 5%. The study finds causality also for demand for broad money and inflation and suggests that the direction of policy to include monetary aggregate targeting is favorable.
Thesis (MPhil) - University of Ghana, 2015
Keywords: Economy; Inflation; Monetary Aggregate; GDP Growth; Money Demand